(untitled) - Christ, Grace Hyslop (New York, 2000)
Includes bibliographical references and indexes; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Bereavement in adolescence; Bereavement in children; Children and death; Grief in adolescence; Grief in children; Parents -- Death -- Psychological aspects; Teenagers and death; Cha mẹ -- Cái chết -- Khía cạnh tâm lý